HTML : the complete reference - Powell, Thomas A. (Berkeley, California : Osborne McGraw-Hill, 1999)
In the COMPLETE REFERENCE series. The second edition is updated to include the latest technologies and new versions of browsers from Microsoft and Netscape. Includes discussions on XML and DHTML along with examples of user interface modifications, object movements and examples of how XML relates to HTML. Contains HTML tags reference material.
Includes index.
Keywords: HTML (DOCUMENT MARKUP LANGUAGE)